2017
DOI: 10.1111/jgs.15106
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Elder Abuse in São Paulo and Rio de Janeiro

Abstract: Elder abuse is prevalent in São Paulo and Rio de Janeiro, but whether concomitants of abuse are cause, effect, or both is unclear because this was a cross-sectional study. These findings highlight the importance of the problem, as well as the need to develop measures to increase awareness, facilitate prevention, and fight against abuse of elderly adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 30 publications
(70 reference statements)
2
13
0
10
Order By: Relevance
“…However, it is consistent with another study which found that EAN prevalence worldwide ranged from 3.2% to 27.5% . In Brazil, 14.4% older adults reported experiences of abuse, while in Mexico, the prevalence was 32.1% . Ultimate comparison across studies remains a challenge due to the heterogeneity in study methods and operational definition.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, it is consistent with another study which found that EAN prevalence worldwide ranged from 3.2% to 27.5% . In Brazil, 14.4% older adults reported experiences of abuse, while in Mexico, the prevalence was 32.1% . Ultimate comparison across studies remains a challenge due to the heterogeneity in study methods and operational definition.…”
Section: Discussionsupporting
confidence: 85%
“…3 In Brazil, 14.4% older adults reported experiences of abuse, while in Mexico, the prevalence was 32.1%. 20,21 Ultimate comparison across studies remains a challenge due to the heterogeneity in study methods and operational definition. For instance, some studies define EAN as occurrences within the past 12 months, while some others-including this study-take into account all abuse episodes from the age of 60.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of EAN in this study was 8.1%. This is lower than the prevalence reported in urban Malaysia (9.6%), Brazil (14.4%), and Mexico (32.1%) . A systematic review found the pooled prevalence estimate of EAN to be 15.7%, and another reported the global prevalence of EAN as ranging between 3.2% to 27.5% .…”
Section: Discussionmentioning
confidence: 79%
“…Embora a violência contra idosos seja um problema de saúde pública global 3 , há pouco conhecimento sobre esse tema em países menos desenvolvidos. Isso pode ser atribuído, entre outros motivos, à escassez de dados epidemiológicos sobre a violência contra idosos 40 . No Brasil, estudos documentaram prevalência da violência contra idosos variando de 10,1 a 21%, sendo de 10,1% 43 e 21% em Camaragibe 44 .…”
Section: Discussionunclassified
“…No presente estudo, 10% dos participantes referiram ter sofrido algum tipo de violência. Essa prevalência é maior do que a encontrada em estudos realizados na Europa 45 (5,6%) e América do Norte 46 (8,1%) e também superior às estimativas de violência doméstica contra idosos divulgadas pela OMS (4 a 6%) 2 , embora seja inferior às taxas encontradas na África e (43,7,%) 47 , Ásia (49,1%) 48 e em outras localidades no Brasil 35,36,[40][41][42][43][44] .…”
Section: Discussionunclassified